2022
DOI: 10.1186/s12933-022-01503-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of magnitude of weight loss and weight variability with mortality and major cardiovascular events among individuals with type 2 diabetes mellitus: a systematic review and meta-analysis

Abstract: Background Weight management is strongly promoted for overweight or obese patients with type 2 diabetes (T2DM) by current guidelines. However, the prognostic impact of weight loss achieved without behavioural intervention on the mortality and cardiovascular (CV) outcomes in diabetic patients is still contested. Methods We searched the PubMed, Embase, and Cochrane Library databases for studies that investigated the association of weight loss or weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 56 publications
1
11
0
1
Order By: Relevance
“…It was also hypothesized that the HP group would result in preferential loss of fat mass compared with FFM, which was also not supported. A recent review suggested that weight loss could increase the risk of mortality for those recently diagnosed with T2D, potentially as a result of a decline in appendicular lean mass [37]. Although appendicular body composition was not analyzed for the present study, whole‐body FFM was only slightly reduced, with no significant differences between groups.…”
Section: Discussionmentioning
confidence: 82%
“…It was also hypothesized that the HP group would result in preferential loss of fat mass compared with FFM, which was also not supported. A recent review suggested that weight loss could increase the risk of mortality for those recently diagnosed with T2D, potentially as a result of a decline in appendicular lean mass [37]. Although appendicular body composition was not analyzed for the present study, whole‐body FFM was only slightly reduced, with no significant differences between groups.…”
Section: Discussionmentioning
confidence: 82%
“…STZ is a glucose analogue and it accumulates in β-cells of the pancreas forming an alkylating agent which brings out the diabetogenic action of this compound 16 . The uncontrolled high blood sugar levels due to STZ-diabetes induction lead to increased urination, excessive thirst, increased metabolism, protein catabolism, and muscle oxidative damage resulting in unintended weight loss 17 . In the present study, a sharp decline in the weight of the diabetic control group could be attributed to the unavailability of glucose to the cells which compels the body to burn fat causing a reduction in body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Copyright © 2023 Korean Endocrine Society www.e-enm.org 303 ated with major weight loss (>10%) among type 2 diabetes patients [9]. Another systematic review and meta-analysis of 14 observational studies and three clinical trials examining behavioral weight changes and cardiovascular disease in patients with type 2 diabetes showed that weight gain was linked to a significantly higher hazard of cardiovascular events and all-cause mortality compared to no weight change [10].…”
Section: Weight Loss and Cardiovascular Risk Reduction In Diabetesmentioning
confidence: 99%